Consumers’ Perceptions of Price Steering in Shopping Online for Tourism - Dr Jean Michel CHAPUIS (Journal of Management Research, 2024)
When confronting discriminations during the buying process, the consumers may perceive unfair transactions and some untrustworthy providers. Price steering is a common manipulation of listing offers tailored to a customer’s request. The consumers receive a same-products list in a different order for the same query on e-shop. The study questions whether its performance is related to discrimination among consumers. This paper mobilizes the theory of Justice to explore perceptions of fairness and trust in the practice of price steering. The proposed framework states that the post-purchase stage reveals perceptions intervening in the effect of price steering on willingness to pay. An experiment with a total 883 respondents is simulating an online shopping. The list of options shown online is manipulated. This study documents the main effect of price steering such as a higher willingness to pay and driving online purchasers toward certain choices. This effect is found to generate up to 20% of extra revenue. The analysis also finds a negative influence on perceptions with no difference between the discriminated segments of the market. Implications for researchers and managers: the pricing schemes should be carefully tailored to maintain fairness, as well as profitability, by considering rate parity across online channels and purchasing experiences.